Comparison of endoscopic ultrasound-directed transgastric endoscopic retrograde cholangiopancreatography outcomes using various technical approaches - Firas Bahdi (Endoscopy International Open, 2022)
Background and study aims Roux-en-Y gastric bypass presents an anatomic challenge for patients needing ERCP. EUS-directed transgastric ERCP (EDGE) offers high clinical success but carries considerable risk of adverse events (AEs) with no standardized technical approach. In our study, we review the safety and efficacy of our various EDGE technical approaches. Patients and methods A retrospective single-center study of all patients who underwent EDGE procedures between February 2018 and November 2019. Primary outcomes included comparing the technical and clinical success, AEs, and lumen-apposing metal stent (LAMS) migration rates per access route (gastrogastric vs jejuno-gastric), number of procedure stages (single-stage vs two-stage), and stent size (15 mm vs 20 mm). Secondary outcomes included LAMS migration characteristics and management. Results Thirty-two EDGE procedures were performed in 29 patients, including 17 single-stage and 15 two-stage procedures, 23 gastrogastric, and nine jejuno-gastric routes, fourteen 15-mm and 17 20-mm LAMS. Overall technical and clinical success rates were 96.9 % and 87.1 %, respectively, without any significant difference between groups. The overall AE rate was (34.4 %) and was significantly lower in the 20-mm LAMS group compared to the 15-mm group (17.6 % vs 57.1 %, P = 0.03). Compared to two-stage procedures, there was no significant difference in AEs with single-stage procedures (35.3 % vs 33.3 %, P = 0.33). The LAMS migration rate was (25 %) with no significant difference between groups. Most migrations were around the index procedure and managed endoscopically (62.5 %). Conclusions EDGE offers high clinical success rates but AE rates remain significant. In our series, a 20-mm LAMS resulted in a significantly lower AE rate than the 15-mm LAMS. Large multicenter studies are recommended to identify technical factors leading to an optimal EDGE procedure.